Storage conditions affect the composition of the lyophilized secretome of multipotent mesenchymal stromal cells - Rogulska, Olena; Vackova, Irena; Prazak, Simon; Turnovcova, Karolina; Kubinova, Sarka; Bacakova, Lucie; Jendelova, Pavla; Petrenko, Yuriy (Scientific reports, 2024)
The widespread use of multipotent mesenchymal stromal cell-derived secretome (MSC-sec) requires optimal preservation methods. Lyophilization offers benefits like concentrating the secretome, reducing the storage volume, and making storage conditions more flexible. This study evaluated the influence of storage duration and temperature on lyophilized MSC-sec. The conditioned medium from Wharton's jelly MSCs was stored at - 80 °C or lyophilized with or without trehalose. Lyophilized formulations were kept at - 80 °C, - 20 °C, 4 °C, or room temperature (RT) for 3 and 30 months. After storage and reconstitution, the levels of growth factors and cytokines were assessed using multiplex assay. The storage of lyophilized MSC-sec at - 80 °C ensured biomolecule preservation for 3 and 30 months. Following 3 month storage at 4 °C and RT, a notable decrease occurred in BDNF, bNGF, and sVCAM-1 levels. Prolonged 30 month storage at the same temperatures significantly reduced BDNF, bNGF, VEGF-A, IL-6, and sVCAM-1, while storage at - 20 °C decreased BDNF, bNGF, and VEGF- A levels. Trehalose supplementation of MSC-sec improved the outcome during storage at 4 °C and RT. Proper storage conditions were crucial for the preservation of lyophilized MSC-sec composition. Short-term storage at various temperatures maintained over 60% of the studied growth factors and cytokines; long-term preservation was only adequate at -80 °C.
Keywords: Trehalose; Cryopreservation; mezenchymální kmenové buňky; Cytokines; teplota; kultivační média speciální; cytokiny; lidé; Secretome; Culture Media, Conditioned; kultivované buňky; kryoprezervace; Mesenchymal Stem Cells; Temperature; Cells, Cultured; Freeze Drying; lyofilizace; trehalosa; sekretom; Humans